2022
DOI: 10.1021/acs.nanolett.2c00168
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electricity Generation from Graphene Microfluidic Channels for Self-Powered Flexible Sensors

Abstract: As a novel energy harvesting method, generating electricity from the interaction of liquid−solid interface has attracted growing interest. Although several functional materials have been carried out to improve the performance of the flowinduced hydrovoltaic generators, there are few reports on influencing the droplet flow behavior to excavate its electricity generation by governing the device structure. Here, the output performance of the graphene microfluidic channel (GMC) structure is ∼13 times higher than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…Moreover, the absence of any obvious electricity response in the pS films further elucidates the necessity of graphene (Figures 3d and S31a−c). 5,11,18 The GS device constructed by EPD-driven SiC wassisted transfer exhibits more favorable output performance due to the freedom from transfer-related contaminants as well as the robust contact between graphene and the SiC w mesh underlayer, which exerts a supportive substrate effect. 14,26 By comparison, pure graphene and traditional transferred GS films demonstrate considerably inferior output performance, which is naturally contrary to the advantages of the EPD process (Figure S31d−i).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the absence of any obvious electricity response in the pS films further elucidates the necessity of graphene (Figures 3d and S31a−c). 5,11,18 The GS device constructed by EPD-driven SiC wassisted transfer exhibits more favorable output performance due to the freedom from transfer-related contaminants as well as the robust contact between graphene and the SiC w mesh underlayer, which exerts a supportive substrate effect. 14,26 By comparison, pure graphene and traditional transferred GS films demonstrate considerably inferior output performance, which is naturally contrary to the advantages of the EPD process (Figure S31d−i).…”
Section: Resultsmentioning
confidence: 99%
“…5 The generation of the generators are capable of yielding high levels of instantaneous power density with relatively facile device configurations, the energy conversion efficiency of hydrovoltaic generators is still being pursued by exploring different low-dimensional functional materials 5−10 and designing distinctive device structures. 11 In addition to the feasibility of substitutional doped graphene to enhance electricity generation, 12,13 it has been demonstrated experimentally and theoretically that the graphene substrate is equally significant for regulating the output performance of graphene-based flow-induced generators. 14−18 Notably, when mentioning the substrate effect of graphene, it inevitably involves the transfer of graphene onto the target substrate to exploit its properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kong et al demonstrated the fabrication of a graphene microfluidic channel (GMC) to regulate droplet movement and they designed a self-powered pressure sensor. 93 The energy generated by redistribution and interaction of the ions in a solution with graphene surface was the working source for the self-powered GMC pressure sensor (Fig. 9(a)).…”
Section: Ionic Solutionsmentioning
confidence: 99%
“…With the rapid development of smart wearable devices, demand for flexible sensors has greatly increased. [1][2][3][4][5] Many previously reported flexible sensors have exhibited broad applications in human motion detection, [6,7] human-machine interfaces, [8,9] pulse monitoring, [10,11] temperature detection, [12,13] electrochemical analysis, [14,15] humidity response, [16,17] and respiratory monitoring. [18,19] For example, a gold nanoparticle thin-film strain sensor was fabricated to monitor human pulse.…”
Section: Introductionmentioning
confidence: 99%